THERMAL ANALYSIS OF PHASE-CHANGE MATERIALS FOR ENERGY STORAGE APPLICATIONS - Syed Yamin Qadri (PT. Radja Intercontinental Publishing, 2024)
Phase-Change Materials (PCMs) are emerging as promising candidates for energy storage due to their ability to store and release significant amounts of thermal energy during phase transitions. This research focuses on the thermal analysis of various PCMs to evaluate their performance in energy storage systems. By examining key parameters such as latent heat capacity, thermal conductivity, and phase transition temperature, the study provides insights into the optimisation of PCMs for efficient energy management. Experimental and computational methods were employed to analyse different types of PCMs, including organic, inorganic, and eutectic materials. The results highlight the trade-offs between thermal performance, stability, and material cost, paving the way for their integration into applications such as building energy systems and renewable energy storage. The findings contribute to developing sustainable and efficient thermal energy storage solutions.